PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG SISI LENGKUNG - Pangalila, Marthen Semuel Toar; Regar, Vivian E.; Monoarfa, Jorry F. (SOSCIED, 2024)
This study aims to determine the difference in student learning outcomes using the Project Based Learning (PJBL) Model is higher than student learning outcomes using Direct Learning in mathematics learning curved side space building material. This type of research is Experimental Research using Posttes Only Control Group Design, this research was conducted at Rurukan Christian Junior High School. The subjects in this study were all students of class IX, where IX-A with 18 students as the experimental class and IX-B with 17 students as the control class, which were randomly selected. From the results of research and data analysis with a real level of 5% (0.05) shows the average value of the experimental class is 81.5 and the average control class is 74.23. Thus it can be seen that student learning outcomes using Project Based Learning (PJBL) are higher in learning mathematics curved side space building material